Periode kritis sorgum dalam persaingan dengan gulma=Critical Period of Sorghum in Weed Competition - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
An experiment was conducted to determine the critical period of sorghum variety UPCA-S1 to weed competition. The field experiment was conducted at KP-4 Kalitirto, University of Gadjah Mada from May to August 2003. It was a single factor experiment evaluating 14 treatments, with varying continuously weedy and weed free period arranged in a Randomized Completely Block Design (RCBD) with three blocks as replications. Statistical analysis of variance and Duncan's New Multiple Range Test (DMRT) 5% was applied. The results showed that critical period of sorghum variety UPCA-Sl in weed competition was 7-21 days after planting, with critical point was 13 days old and it could reduce yield up to 75,22%. The critical threshold level was 1,21 g/0,25 m2 of weed density.